Microdistribution of faunal assemblages at deep-sea hydrothermal vents in the Southern Ocean. - Leigh Marsh (PLoS ONE, 2012)
Chemosynthetic primary production by microbes supports abundant faunal assemblages at deep-sea hydrothermal vents, with zonation of invertebrate species typically occurring along physico-chemical gradients. Recently discovered vent fields on the East Scotia Ridge (ESR) in the Southern Ocean represent a new province of vent biogeography, but the spatial dynamics of their distinct fauna have yet to be elucidated. This study determines patterns of faunal zonation, species associations, and relationships between faunal microdistribution and hydrothermal activity in a vent field at a depth of 2,400 m on the ESR. Remotely operated vehicle (ROV) dives obtained high-definition imagery of three chimney structures with varying levels of hydrothermal activity, and a mosaic image of >250 m(2) of seafloor co-registered with temperature measurements. Analysis of faunal microdistribution within the mosaiced seafloor reveals a consistent pattern of faunal zonation with increasing distance from vent sources and peak temperatures. Assemblages closest to vent sources are visibly dominated by a new species of anomuran crab, Kiwa n. sp. (abundance >700 individuals m(-2)), followed by a peltospiroid gastropod (>1,500 individuals m(-2)), eolepadid barnacle (>1,500 individuals m(-2)), and carnivorous actinostolid anemone (>30 individuals m(-2)). Peripheral fauna are not dominated by a single taxon, but include predatory and scavenger taxa such as stichasterid seastars, pycnogonids and octopus. Variation in faunal microdistribution on chimneys with differing levels of activity suggests a possible successional sequence for vent fauna in this new biogeographic province. An increase in δ(34)S values of primary consumers with distance from vent sources, and variation in their δ(13)C values also indicate possible zonation of nutritional modes of the vent fauna. By using ROV videography to obtain a high-resolution representation of a vent environment over a greater extent than previous studies, these results provide a baseline for determining temporal change and investigations of processes structuring faunal assemblages at Southern Ocean vents.